Understanding the oceanographic dynamics of the Isla Chañaral baleen whale feeding ground, (Humboldt Archipelago, Northern Chile) to extend habitat protection - Buchan, Susannah J.; Ramos, Marcel; Oyanadel, Jorge; Santos-Carvallo, Macarena; Bedriñana-Romano, Luis; Valladares, María; Maldonado, Marinella; Astudillo, Orlando; Sepúlveda, Maritza; Pearce, Steve; Olavarría, Carlos (Frontiers in Marine Science, 2024)
Off Northern Chile, baleen whales use the area around Isla Chañaral as a feeding ground where they forage on euphausiids. Isla Chañaral is part of the highly productive Humboldt Archipelago (∼ 28°S-29°S) within the Humboldt Current System (HCS). In this study, we seek to understand the sub-mesoscale spatial distribution of fin and blue whales and their prey around Isla Chañaral using systematic and opportunistic visual sighting data of whales and systematic acoustic backscatter data of zooplankton from an Acoustic Zooplankton and Fish Profiler (AZFP); and to examine the oceanographic dynamics of the wider Humboldt Archipelago area with remote-sensing oceanographic data. We completed a total of 512.6 km of survey effort over 20 days in 2018 and 318.3 km over 16 days in 2019 collecting systematic whale sighting and backscatter data. A total of 42 fin whales, 0 blue whales and 66 unidentified whales were sighted in 2018, and 7 fin whales, 3 blue whales and 12 unidentified whales were sighted in 2019. Observed spatial distribution of backscatter and whales was strongly associated with a bathymetric feature, i.e., the submarine canyon that curves around Isla Chañaral. Generalized Additive Models showed that fin whale presence was associated with high levels of backscatter and shallow depths similar to those of the canyon. We found that long-term average geostrophic currents form a recirculation system between 28°S and 31°S that can transport nutrient-rich upwelled surface waters back towards the Humboldt Archipelago and contribute to high biological productivity in this area. However, in summer 2019 geostrophic flow occurred away from the coast and a warm low-productivity spring explained low backscatter and whale sightings around Isla Chañaral. The unique oceanographic features of Isla Chañaral and the Humboldt Archipelago that contribute to high concentrations of Endangered baleen whales and their prey justify the extension of the Isla Chañaral Marine Reserve to include the canyon between the mainland and the island, and the implementation of a Multiple Use Marine Protected Area for the entire Humboldt Archipelago area that explicitly protects this critical feature.